Green synthesis and antibacterial potency of Ag/CuO/ZnO nanoparticles derived from Psidium guajava L. extracts - Bhardwaj, Richa; Naruka, Devyani; Kapoor, Neha; Gambhir, Lokesh (Plant Science Today, 2024)
Nanoparticles, characterized by their unique physicochemical properties, represent a significant frontier in interdisciplinary research, particularly within the realms of biomedicine and environmental science. This investigation delves into the eco-friendly synthesis of silver (Ag), copper oxide (CuO) and zinc oxide (ZnO) nanoparticles utilizing extracts derived from Psidium guajava L. The utilization of these botanical extracts presents a sustainable alternative to traditional nanoparticle fabrication methodologies, aligning with global sustainability imperatives and fostering environmentally conscious practices. The escalating global nanoparticle market, valued at over $30 billion in 2020 and projected to surpass $90 billion by 2027, underscores the economic significance and industrial relevance of nanoparticle research. This research trajectory fuels innovation across a spectrum of sectors, including healthcare, cosmetics and environmental remediation. The commercialization of nanoparticle-based products not only drives substantial revenue streams but also catalyzes advancements in research, development and manufacturing endeavors. Drawing upon aqueous extracts sourced from P. guajava., leaves and fruits, this study capitalizes on their inherent phytochemical composition to serve as stabilizing, reducing and capping agents during nanoparticle synthesis. Employing state-of-the-art characterization techniques such as UV-Vis spectroscopy, FTIR spectroscopy, FE-SEM and EDS facilitates a comprehensive analysis of the synthesized nanoparticles' physicochemical attributes. Assessment of the nanoparticles' antibacterial efficacy against gram-positive (Bacillus subtilis, Staphylococcus aureus) and gram-negative (Escherichia coli, Proteus vulgaris) bacterial strains reveals compelling results. Minimum inhibitory concentrations (MIC) elucidate notable efficacy, notably against P. vulgaris (3.75 mg/mL), S. aureus (7.5 mg/mL) and B. subtilis (10 mg/mL and 12.5 mg/mL), indicative of their potential biomedical applications in combating microbial infections.